Genomic and Molecular Landscape of DNA Damage Repair Deficiency across The Cancer Genome Atlas. - Knijnenburg, Theo A.; Wang, Linghua; Zimmermann, Michael T.; Chambwe, Nyasha; Gao, Galen F.; Cherniack, Andrew D.; Fan, Huihui; Shen, Hui; Way, Gregory P.; Greene, Casey S.; Liu, Yuexin; Akbani, Rehan; et al. (Cell Reports, 2018)
DNA damage repair (DDR) pathways modulate cancer risk, progression, and therapeutic response. We systematically analyzed somatic alterations to provide a comprehensive view of DDR deficiency across 33 cancer types. Mutations with accompanying loss of heterozygosity were observed in over 1/3 of DDR genes, including TP53 and BRCA1/2. Other prevalent alterations included epigenetic silencing of the direct repair genes EXO5, MGMT, and ALKBH3 in ∼20% of samples. Homologous recombination deficiency (HRD) was present at varying frequency in many cancer types, most notably ovarian cancer. However, in contrast to ovarian cancer, HRD was associated with worse outcomes in several other cancers. Protein structure-based analyses allowed us to predict functional consequences of rare, recurrent DDR mutations. A new machine-learning-based classifier developed from gene expression data allowed us to identify alterations that phenocopy deleterious TP53 mutations. These frequent DDR gene alterations in many human cancers have functional consequences that may determine cancer progression and guide therapy.
EVALuna2:35948